2009
DOI: 10.1111/j.1600-0404.2009.01306.x
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical pulmonary dysfunction in spinocerebellar ataxias 1, 2 and 3

Abstract: The present study showed subclinical restrictive type of pulmonary dysfunction in SCA, and possible presence of upper airway obstruction. Chest physiotherapy and breathing exercises should be introduced early in management of SCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…The present study found a reduced BPV in SCA patients compared to the controls, which could probably be attributed to impaired ventilation in these patients. A previous report shows pulmonary dysfunction and reduced respiratory muscle strength in SCA1 and SCA2 patients . This lack of integrity of respiratory muscles caused by dysfunctional cerebellar coordination (as proved by cerebellectomy) is an important feature in SCA patients .…”
Section: Discussionmentioning
confidence: 92%
“…The present study found a reduced BPV in SCA patients compared to the controls, which could probably be attributed to impaired ventilation in these patients. A previous report shows pulmonary dysfunction and reduced respiratory muscle strength in SCA1 and SCA2 patients . This lack of integrity of respiratory muscles caused by dysfunctional cerebellar coordination (as proved by cerebellectomy) is an important feature in SCA patients .…”
Section: Discussionmentioning
confidence: 92%
“…Hence, the mild cortical and hippocampal developmental defects in the 14-3-3ε +/− mice are unlikely to be responsible for the nonrescued life span phenotype in Sca1 154Q/+ ; 14-3-3ε +/− mice. In the course of trying to understand the cause of death, we uncovered a respiratory dysfunction that had not been reported previously in the Sca1 knock-in mice but is documented in human patients (14). While we were investigating this phenotype, four mice (two Sca1 154Q/+ and two Sca1 154Q/+ ; 14-3-3ε +/− mice) died within 2 to 4 d of our last recording.…”
Section: Discussionmentioning
confidence: 99%
“…SCA1 usually causes onset of slowly progressive gait ataxia in midlife to late life, eventually impairing overall motor coordination and producing dysarthria, hypometric saccades, weight loss, respiratory dysfunction, and premature death (13,14). Cerebellar Purkinje cells are the first to be affected, which accounts for the presenting ataxia, but the pons and brainstem are also prominently involved.…”
mentioning
confidence: 99%
“…Even though initial SCA studies have mostly focused on movement disorders, some have addressed pulmonary function in patients with SCAs and other neurodegenerative diseases like Parkinson's disease (PD) and Huntington's disease (HD) 9,20,21 . Sriranjini et al 9 pointed out that the lack of respiratory manifestations in SCA could explain the small number of studies in this area. These authors observed subclinical restrictive pulmonary dysfunction in individuals with ataxia and recommended early management with respiratory physical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Sriranjini et al 9 showed a prevalence of restrictive pulmonary dysfunction and upper airway obstruction in patients with SCA1, SCA2, and SCA3; compared with controls, these patients presented significantly lower parameters of total lung volume and respiratory muscle strength. The authors observed subclinical pulmonary dysfunction in all subtypes of SCA analyzed, but the correlation between lung function and disease parameters occurred only in patients with SCA3.…”
mentioning
confidence: 98%